2009
DOI: 10.1103/physrevlett.103.232701
|View full text |Cite
|
Sign up to set email alerts
|

Modern Rutherford Experiment: Tunneling of the Most Neutron-Rich Nucleus

Abstract: A modern variation of the Rutherford experiment to probe the tunneling of exotic nuclear matter from the measurement of the residues formed in the bombardment of (197)Au by extremely neutron-rich (8)He nuclei is presented. Using a novel off-beam technique the most precise and accurate measurements of fusion and neutron transfer involving reaccelerated unstable beams are reported. The results show unusual behavior of the tunneling of (8)He compared to that for lighter helium isotopes, highlighting the role of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 30 publications
6
111
0
Order By: Relevance
“…The experimental data of this system are obtained from Ref. [32]. In this case also, we had found that the inclusion of the coupling enhances the semiclassical calculations markedly above and below the Coulomb barrier compared with the measured data, while the CC calculations have very slight improvement below the Coulomb barrier, but still far from the measured data.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The experimental data of this system are obtained from Ref. [32]. In this case also, we had found that the inclusion of the coupling enhances the semiclassical calculations markedly above and below the Coulomb barrier compared with the measured data, while the CC calculations have very slight improvement below the Coulomb barrier, but still far from the measured data.…”
Section: Resultsmentioning
confidence: 77%
“…a for the total fusion cross section r fus (mb), and b for the fusion barrier distribution D fus (mb/ MeV), and the arrow represents the position of the Coulomb barrier V b (a) (b) Fig. 2 The comparison of the semiclassical and full quantum mechanical calculations using SCF code (blue curves) and CCFull code (black curves) with the experimental data (black filled circles) [32] for 8 He þ 197 Au system. a for the total fusion cross section r fus (mb), and b for the fusion barrier distribution D fus (mb/ MeV), and the arrow represents the position of the Coulomb barrier V b experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…This will enable several activation measurements at different energies to be simultaneously undertaken with a fixed beam energy. This has already been done in previous similar experiments [40,42,[44][45][46][47][48][49][50], thus reducing the beam time needed for the measurement. However, using a stack introduces problems which can complicate the interpretation of the activation results.…”
Section: B Target Activationmentioning
confidence: 70%
“…For reactions induced by weakly bound nuclei [16,17,25,26,27,28,39,40,41] and exotic nuclei [18,19,20,21,22,38,42,43,44,45,46], the breakup channel is open and plays a key role in the fusion process near the Coulomb barrier similarly to the transfer-channel coupling described in the previous section. It is therefore appropriate to use the Continuum-Discretized Coupled-Channel (CDCC) approach [47,48,49,50] to describe the influence of the breakup channel in both the elastic scattering and the fusion process at sub-barrier energies.…”
Section: LI + 59 Co and 7 Li + 59 Co Reactionsmentioning
confidence: 99%
“…Recent studies with Radioactive Ion Beams (RIB) indicate that the halo nature of 6,8 He [18,19,20,21,22], for instance, does not enhance the fusion probability as anticipated. Rather the prominent role of one-and two-neutron transfers in 6,8 He induced fusion reactions was definitively demonstrated.…”
Section: Introductionmentioning
confidence: 99%